2008
DOI: 10.1074/jbc.m802914200
|View full text |Cite
|
Sign up to set email alerts
|

Differences in a Conformational Equilibrium Distinguish Catalysis by the Endothelial and Neuronal Nitric-oxide Synthase Flavoproteins

Abstract: Nitric oxide (NO) is a physiological mediator synthesized by NO synthases (NOS).Despite their structural similarity, endothelial NOS (eNOS) has a 6-fold lower NO synthesis activity and 6 -16-fold lower cytochrome c reductase activity than neuronal NOS (nNOS), implying significantly different electron transfer capacities. We utilized purified reductase domain constructs of either enzyme (bovine eNOSr and rat nNOSr) to investigate the following three mechanisms that may control their electron transfer: (i) the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
153
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(166 citation statements)
references
References 65 publications
(115 reference statements)
12
153
1
Order By: Relevance
“…The mean values can also fluctuate depending on the dwell times of individual states over the course of the collection time (i.e., shorter-lived conformations may appear more times during the collection period). Nevertheless, our study provides, to our knowledge, the first dynamics-based, single molecule demonstration that under physiologic conditions, CaM binding shifts the conformational distribution of nNOSr toward more open states, consistent with results from ensemble-based studies (26,27,34,37), and we additionally show that CaM narrows the conformational population distribution of nNOSr.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…The mean values can also fluctuate depending on the dwell times of individual states over the course of the collection time (i.e., shorter-lived conformations may appear more times during the collection period). Nevertheless, our study provides, to our knowledge, the first dynamics-based, single molecule demonstration that under physiologic conditions, CaM binding shifts the conformational distribution of nNOSr toward more open states, consistent with results from ensemble-based studies (26,27,34,37), and we additionally show that CaM narrows the conformational population distribution of nNOSr.…”
Section: Resultssupporting
confidence: 69%
“…two to four discreet conformational populations in NOS enzymes and in related flavoproteins, and in some cases, have also estimated the distances between the bound FAD and FMN cofactors in the different species (26,36,37,39,40), and furthermore, have confirmed that CaM shifts the NOS population distribution toward more open conformations (34,36,45). Although valuable, such ensemble-averaged results about conformational states cannot explain how electrons transfer through these enzymes, or how CaM increases the electron flux in NOS, because answering these questions requires a coordinate understanding of the dynamics of the conformational fluctuations.…”
Section: Significancementioning
confidence: 71%
See 2 more Smart Citations
“…In this mechanism, CaM binding releases the FMN subdomain from its interaction with the FAD/NADPH subdomain, allowing the FMN subdomain to transfer electrons to the oxidase domain (or alternative acceptors such as cytochrome c; Fig. 1B) (34)(35)(36)(37)(38)(39). Indeed, in CaM-bound nNOS, many 2D class averages were observed whereby the FMN subdomain is visualized as a blurred cloud of density (Fig.…”
Section: Discussionmentioning
confidence: 99%